Reconceptualising the regulatory regime for factoring in Tanzania in support of small and medium enterprises - Ngobeni, Tinyiko (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2025.